Formulation and Storage Properties of Trasparent Soap Prepared From Enzymatically and Nonenzymatically Treated Palm-Based Materials - Koh, Soo Peng (2004)
The study on the physical and chemical properties of 28 samples of commercial transparent soap provided valuable information that could be used as a guideline in the preparation of palmbased transparent soap formulation. Most of the commercial transparent soaps had good transparency (above 0.8) with a moderate total f%Iy matter of between 40% and 60%. They were mostly superfatted products and showed good foamability and hardness with a penetration value of less than 5 mm Differences in titer, acid and iodine values affected the ability of different palm based fatty acid in accepting the amount of sodium salt into soap formulation and the hardness property. The proper combination of triethanolarnine, glycerol and sugar solution played an important role in determining the transparency, hardness, foamability and moisture content of the soap produced. Transparent soap bar made from blends of distilled palm stearin fatty acid with ricinoleic acid wvered a wide range of acceptability for triethanolamine (20-90%) with low amount of sugar solution (less than 30%) and less than 70% of glycerol. However, in blends of distilled palm oil fatty acid-based soap with ricinoleic acid, the transparerrt soap region ranged between 40% and 80% triethanolamine, less than 40% of glycerol and between 20% to 50% of sugar solution Both blends of distilled palm htty acid-based transparent soap had transparency reading above 0.8 and penetration value of less than 8 nun with the majority of moisture content of soap fklling between 15% and 20%. In the region of low percentage of triethanolamine (OO/i-20%) with 80-100% of glycerol and sugar solution used, both distilled palm htty acids used in soap formulation produced soft and gummy opaque soap. Lipase-catalysed acidolysis is a vital tool to tailor-make refined, bleached and deodorised palm oil (RBD palm oil) enriched with ricinoleic acid (RA). Lipozyme IM60 lipase performed better (12.33% FWD4 hours) than Pseudomnas sp iipase (2.59% RN24 hours) as it was able to incorporate more ricinoleic acid into RBD palm oil at a shorter time. The alteration in trigly-de composition of acidolysed oil had led to the changes in their slip melting point, iodine value, solid fat content, crystallisation and melting behaviour and also the viscosity of the acidolysed oil produced. The differences in sodium salt content used in different fatEy raw material-based soap formulation had caused an effect on the transparency, tow fatty matter, penetration value, chloride content and foamability of soap d e . In general, the presence of ricinoleic acid in the blends of distilled palm oil fatty acid soap, blends of distilled palm stearin fatty acid soap and acidolysed oil-based soap assisted in improving the soap transparency, especially when high mtenfs of sodium salt were used in the soap fmulatioa